EFISIENSI RELATIF BELANJA SEKTOR PUBLIK TERHADAP KESEJAHTERAAN MASYARAKATDI JAWA TIMUR: PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - Pristian Putri, Rahma Dewi; Prasetyia, Ferry (Journal of Development Economic and Social Studies, 2023)
This study aims to measure the relative efficiency of public sector spending (health, education, and the economy) and determine the effect of the relative efficiency of public sector spending (health, education, and economy) as well as GRDP per capita and the Open Unemployment Rate (TPT) as control variables on the Human Development index (HDI) and Inclusive Economic Development Index (IPEI) in the East Java region in 2016-2020. This study uses the Data Envelopment Analysis (DEA) method and panel data regression analysis. The results showed that Batu City, Mojokerto City, and Blitar City each consistently performed relatively efficiently in health, education, and economic spending during the 2016-2020 period. In this case, the efficiency of public sector spending is indeed needed in improving people's welfare. The government is expected to improve the allocation of public sector spending that is more oriented towards the quality of health, education, and basic public infrastructure so that it not only meets the quantity target but also the quality target.